Out-of-Pocket Expenditures for Contraceptives During State Medicaid Expansion, 2013-2016. Issue 4 (10th April 2022) - Brant, Ashley R.; Batur, Pelin; Arrigain, Susana; Lopez, Rocio; Farrell, Ruth M.
Abstract : From 2013 through 2016, 38% of women with contraceptive prescriptions reported out-of-pocket expenditures, averaging $216 annually.